The role of EGFR and ErbB family related proteins in the oligodendrocyte specification in germinal niches of the adult mammalian brain - Galvez-Contreras, Alma Y.; Quinones-Hinojosa, Alfredo; Gonzalez-Perez, Oscar (Frontiers in Cellular Neuroscience, 2013)
In the adult brain, multipotent progenitor cells have been identified in three areas: the ventricular-subventricular zone (VZ-SVZ), adjacent to the striatal wall of the lateral ventricles, the subgranular zone (SGZ), located at the dentate gyrus of the hippocampus and the subcallosal zone (SCZ), located between the corpus callosum and the CA1 and CA2 regions of the hippocampus. The neural progenitor cells of these regions express the epidermal growth factor receptor (EGFR, ErbB-1 or HER1). EGF, the most important ligand for the EGFR, is a potent mitogenic agent that stimulates proliferation, survival, migration and differentiation into the oligodendrocyte lineage. Other ErbB receptors also activate several intracellular pathways for oligodendrocyte specification, migration and survival. However the specific downstream pathways related to oligodendrogenesis and the hierarchic interaction among intracellular signaling cascades is not well-known. We summarize the current data regarding the role of EGFR and ErbB family signaling on neural stem cells and the downstream cascades involved in oligodendrogenesis in the neurogenic niches of the adult brain. Understanding the mechanisms that regulate proliferation, differentiation, migration of oligodendrocytes and myelination is of critical importance for the field of neurobiology and constitutes a crucial step in the design of stem-cell-based therapies for demyelinating diseases.